2011
DOI: 10.1210/en.2010-0981
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Play an Essential Role in IGF-I Signaling and IGF-I-Induced Myocyte Hypertrophy in C2C12 Myocytes

Abstract: IGF-I induces skeletal muscle hypertrophy by stimulating protein synthesis and suppressing the protein degradation pathway; the downstream signaling pathways Akt-mammalian target of rapamycin (mTOR)-p70-kDA-S6-kinase (p70S6K), and Forkhead box O1 (FoxO1) play essential roles in this regulation. Reactive oxygen species (ROS) modulate the signaling of various growth factors via redox regulation. However, the role of ROS in IGF-I signaling is not fully understood. In this study, we investigated whether ROS regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 38 publications
4
62
0
Order By: Relevance
“…Furthermore, RNS and ROS serve as important signalling molecules in mitochondrial biogenesis [6] and glucose transport [7,8], and possibly muscle hypertrophy [9]. Indeed, the modification of ROS metabolism in a number of human exercise studies through the use of pharmaceutical doses of antioxidant vitamins has blunted the expected physiological response to the exercise bout [10] and the adaptation to the exercise stimulus in some [6,8], but not all studies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RNS and ROS serve as important signalling molecules in mitochondrial biogenesis [6] and glucose transport [7,8], and possibly muscle hypertrophy [9]. Indeed, the modification of ROS metabolism in a number of human exercise studies through the use of pharmaceutical doses of antioxidant vitamins has blunted the expected physiological response to the exercise bout [10] and the adaptation to the exercise stimulus in some [6,8], but not all studies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Ozone inhalation itself caused increases in the IGF-I expression and Akt phosphorylation at 7 and 15 days, probably to prevent cell death caused by oxidative stress in dentate gyrus. Previous studies that shown ROS are capable to activate IGF-I and Akt [22,25,26]. In this sense, the IGF and Akt activation might modulate the cell survival or death in an oxidativestress in a dependent manner [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…For transient transfection, C2C12 cells were seeded onto six-well polycarbonate plates at a density of 5 ϫ 10 4 cells/well and transfected 6 h later with 50 nM small interfering (si)RNA against mouse NOX2 (sense, 5=-CGGUGACAAUGAGAACGAAtt-3=, antisense, 5=-UUCGUUCUCAUUGUCACCGat-3=) and mouse angiotensinogen (Agt) (sense, 5=-CGCAUGUACAAGAUGCUGAtt-3=, antisense, 5=-UCAGCAUCUUGUACAUGCGga-3=), or a control scrambled siRNA in antibiotic-free medium plus 10% FBS using Lipofectamine RNAiMAX Reagent (Invitrogen, Carlsbad, CA) according to the manufacturer's instructions (15). All siRNAs were purchased from Ambion (Austin, TX).…”
Section: Western Blot Analysismentioning
confidence: 99%